Investigation of the role of vitamin D metabolism in South African breast cancer patients using a pathology-supported genetic testing platform - Okunola, Abisola Oyedele (Stellenbosch : Stellenbosch University., 2020)
Thesis (PhD)--Stellenbosch University, 2020.